1997
DOI: 10.1002/elps.1150181405
|View full text |Cite
|
Sign up to set email alerts
|

Free‐flow electrophoretic analysis of endosome subpopulations of rat hepatocytes

Abstract: The separation of functional early and late endosomes from other cellular compartments by free-flow electrophoresis (FFE) has been previously demonstrated in nonpolarized cells. Here, using 125I-labeled anti-secretory component antibodies ([125I]SC Ab) and FITC-labeled asialoorosomucoid (FITC-ASOR) as markers of the transcytotic and lysosomal pathway, respectively, we demonstrate the separation of three distinct endosome subpopulations from polarized rat hepatocytes. Internalization of both markers at 16 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…Our results suggest that the endosome populations labeled by the fluid-phase marker dextran are early endosomes and late endosomes since they colocalize with typical markers for the recycling and lysosomal pathway, respectively. Although we have shown that transcytotic endosomes can be separated from early and late endosomes [37], no fluid-phase marker peak was observed at a position corresponding to transcytotic vesicles. This result does not exclude localization of FITCdextran in the endosome population involved in transcytosis, but indicates that only a minor fraction of endocytosed marker enters the transcytotic pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Our results suggest that the endosome populations labeled by the fluid-phase marker dextran are early endosomes and late endosomes since they colocalize with typical markers for the recycling and lysosomal pathway, respectively. Although we have shown that transcytotic endosomes can be separated from early and late endosomes [37], no fluid-phase marker peak was observed at a position corresponding to transcytotic vesicles. This result does not exclude localization of FITCdextran in the endosome population involved in transcytosis, but indicates that only a minor fraction of endocytosed marker enters the transcytotic pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Endosomes were labeled in the isolatedperfused rat liver using pulse-chase conditions based on the transport kinetics of ASOR and pIgA, as determined above and in previous investigations [9,20,35,[43][44][45].…”
Section: Ffe Separates Common Early From Distinctmentioning
confidence: 99%
“…Kinetically early endosomes labeled with 125 I-pIgA (1 min; peak fraction #42) could be resolved from late transcytotic endosomes labeled with FITC-pIgA (10 min; peak fraction #44), the latter being thus shifted slightly more towards the anode. A minor peak of pIgA, found at fraction #34, presumably represents pIgA still bound to the plasma membrane [35].…”
Section: Ffe Separates Common Early From Distinctmentioning
confidence: 99%
See 2 more Smart Citations